Legal Analysis of Marine Space Utilization for Tin Mining Based on Total Suspended Solids at Rebo Beach, Bangka - Astriyani; Veni Gambini Tampubolon; Zahra Syifa Alamsyah; Rezha Yusa Andika Andika (Universitas Negeri Semarang, 2026)
Tin mining on Rebo Beach, Bangka Regency, has triggered conflicts over marine space use and caused significant degradation of the coastal ecosystem. This unauthorized tin mining (PETI) encroaches on an area legally designated for marine tourism development under Bangka Belitung Islands Provincial Regulation No. 3 of 2020. This study was conducted to analyze spatial use inconsistencies and measure their impact on coral reef degradation. The method used is an interdisciplinary normative-empirical approach that integrates legal approaches (Statute, Case, and Conceptual Approaches) with oceanographic analysis (Spatial Evidence Approach), based on spatiotemporal satellite data and field surveys, as scientific evidence of the impacts of tin mining on Rebo Beach. The research results indicate multidimensional inconsistencies in marine spatial use, encompassing spatial function, zoning, legality, and ecological aspects due to the absence of a Marine Spatial Planning Permit (KKPRL), Mining Business License (IUP), and Environmental Impact Assessment (AMDAL). Sedimentation from mining tailings has driven TSS levels to 63 mg/L in 2024, exceeding the 20 mg/L threshold for coral reef waters under Government Regulation No. 22 of 2021. Monsoon dynamics trap suspended sediments in the nearshore zone, reducing light penetration and contributing to coral mortality in 2024. Addressing coastal degradation requires strengthening ecosystem-based marine spatial planning through KKPRL review, technology-based spatial monitoring, diversification of the blue economy, strict law enforcement, and environmental restoration obligations.